BIAŁYSTOK UNIVERSITY OF TECHNOLOGY, FACULTY OF ELECTRICAL ENGINEERING - DEVELOPMENT AND NEW CHALLENGES - Butryło, Bogusław (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2015)
The paper gives a glance on history and current educational offer of the Faculty of Electrical Engineering of Białystok University of Technology. Some leading areas of electrical technologies worked out on the faculty and some new challenges in R&D are presented.